Literasi Wakaf Uang Berbasis Masjid: Literation of Cash Waqf based On Mosque - Acep Zoni Saeful Mubarok (Direktorat Jenderal Bimbingan Masyarakat Islam, 2021)
The purpose of this study is to examine whether mosque can be used effectively to build cash waqf literacy. Then what strategy should be used in utilizing the mosque as a money literacy center. The reason is the mosque gathering place for Muslim and the center of Muslim community activities in all respects. The method uses in this study is a descriptive qualitative sourced from literature review. The results and findings obtain from this study are the strategies in cash waqf literacy based on mosque, it can be carried out in the following: first, building cooperation with organizations that have the duties and functions of mosque development, namely the Indonesian Mosque Council (DMI), the Taklim Council Coordinating Board Mosque (BKMM) and Mosque Youth Communication Agency (BKPRMI). Second, compiling material for taklim and sermon on cash waqf issues so that they become material provisions for preachers (Da'i and Khatib) and third, organizing Training of Trainers (TOT) for preachers (Da'i dan Khatib).